Current Advances in Immunotherapy for Acute Leukemia: An Overview of Antibody, Chimeric Antigen Receptor, Immune Checkpoint, and Natural Killer - Shang, Yufeng; Zhou, Fuling (Frontiers in Oncology, 2019)
Recently, due to the application of hematopoietic stem cell transplantation and small molecule inhibitor, the survival of acute leukemia is prolonged. However, the 5 year survival rate remains low due to a high incidence of relapse. Immunotherapy is expected to improve the prognosis of patients with relapsed or refractory hematological malignancies because it does not rely on the cytotoxic mechanisms of conventional therapy. In this paper, the advances of immunotherapy in acute leukemia are reviewed from the aspects of Antibody including Unconjugated antibodies, Antibody-drug conjugate and Bispecific antibody, Chimeric Antigen Receptor (CARs), Immune checkpoint, Natural killer cells. The immunological features, mechanisms and limitation in clinic will be described.